Codification of the contour of the visual image to acoustics patterns and its decoding by blind. - Martínez y Cárdenas, José Rodolfo; Menchaca García, Felipe Rolando; Berrón Lara, Virginia (Rev. Téc. Fac. Ing. Univ. Zulia, 2013)
In this paper is proposed the developmentÂ´s first phase of a conceptual model for a non-invasive prosthesis for helping blind people to obtain information about the shape of objects. The prosthesis has been called “Acoustic Viewer”. It is based on an encoding of digital image contours into an acoustic pattern which is conceptually simpler than those are found in previous papers. The digital imaging processing algorithms and the method for transforming image into sound using CSound are described here. In order to evaluate coding”™s suitability were chosen 33 (basic) figures, which are formed of straight lines and curves. A training course in their decoding was designed and an experiment with two groups of people, the first consisting only of blind people and the second consisting of people with normal vision, who were trained and finally they participated in a random trial to assess their acquired ability to decoding these patterns. Our results show that both groups developed the same ability for decoding the proposed patterns. This paper shows “Acoustic Viewer” could help blind people.